Process modification of protien-enriched coconut residue flour using low fat coconut residue flour and F-89 as inoculum - Mabunga, Ricardo Frederic I.; De Leon, Sonia Y. (1995.)
This study was done to improve the process of producing protein-enriched coconut residue flour (PECRF) using dry-extraction processed coconut residue flour or low-fat CRF as substrate and F-89 as inoculum. The first phase involved the proximate analysis of low-fat coconut residue flour (low-fat CRF). Results showed that the dry-extraction process was effective in reducing fat from 36.16% to 18.39% dry basis. The second phase involved the optimization of the substrate to water ratio and the level of the F-89inoculum in the production of PECRF using the low-fat CRF. Among the combination of substrate-to-water ratios of 1:0.5, 1:1 and 1:1.5 and levels of inoculum of 10^4, 10^5 and 10^6, the ratio 1:1 at 10^4 inoculum level gave the highest protein level at 21.6357%. The levels of inoculum higher than 10^4 gave no significant effect on the protein contents of the low-fat PECRF therefore increasing levels of inoculum above this is not necessary.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut flour